A realistic bridge towards European banking union - Nicolas Véron (Bruegel, 2013)
New obstacles to the European banking union have emerged over the last year, but a successful transition remains both necessary and possible. The key next step will be in the second half of 2014, when the European Central Bank (ECB) will gain supervisory authority over most of Europe's banking system. This needs to be preceded by a rigorous balance sheet assessment that is likely to trigger significant bank restructuring, for which preparation has barely started. It will be much more significant than current discussions about a bank resolution directive and bank recapitalisation by the European Stability Mechanism (ESM). The 2014 handover, and a subsequent change in the European treaties that will establish the robust legal basis needed for a sustainable banking union, together define the policy sequence as a bridge that can allow Europe to cross the choppy waters that separate it from a steady-state banking policy framework.
Keywords: 330; Finanzsystem; Bankenaufsicht; Eurozone; EU-Staaten